E-business designing interface "petani sejahtera" based on mobile application - Putra, Gilang Pratama; Wibowo, Ari Purno Wahyu (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The monitoring information system is an Android application that was developed to facilitate the distribution of harvests in order to prevent the accumulation of unused crops and the subsequent waste that results from this accumulation. The goal of this study is to determine how successful the features of the “Petani Sejahtera” application were when it came to their implementation. A qualitative approach that takes a descriptive stance is taken with the research that was carried out in this study. This research can be said to follow the targets expected by various parties related to deciphering the data that was collected and then summarizing and sorting it into features based on the methods that were used, the results that were obtained, and the discussions that were held because of those methods and results. The "Petani Sejahtera" application feature is going to undergo additional development in the near and distant futures.